Respiratory symptoms and their determinants among adult women in an urban slum area of Delhi - Arora, Shweta; Rasania, Sanjeev Kumar; Bachani, Damodar; Gandhi, Asha; Chhabra, Sunil K (Indian Journal of Community Health, 2017)
Background: Globally, respiratory disorders accounted for 7.4% deaths, out of total deaths during the year 2015. Aim & Objective: - To estimate the magnitude of respiratory symptoms and their determinants in adult women of 18-59 years. Material & Methods: A cross sectional study was conducted among 500 women of 18-59 years in an urban slum of Delhi. Assessment of respiratory symptoms was done using questionnaire and observations on environmental conditions. Results: Overall prevalence of major respiratory symptoms was 24.8% in the study population. Dyspnea, chronic cough, chronic phlegm, wheeze was observed in 14.2%, 5.6%, 2.4% and 2.6% respectively.